A Systematic Analysis of English Language Use among Healthcare Professionals in the Workplace - Hasna Bunga Pratiwi Hasna Bunga; Oktavia Ika Rahayu Via; Salma Mahdiana Moeren Salma; Annisa Ayu Dwi Pradipta (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study presents a systematic qualitative analysis of English language use among healthcare professionals in multilingual workplace environments. Drawing on a sociolinguistic and pragmatic framework, the review synthesizes empirical literature to explore how English functions not only as a medium of communication but also as a marker of power, inclusion, and professional legitimacy. The findings reveal that English is institutionalized as the dominant working language in many healthcare settings, contributing to both standardization and social stratification. Key themes include the role of English in shaping linguistic hierarchies, communication barriers among staff, the tension between formal language policies and informal practices, and strategies of adaptation such as translating. While English proficiency often dictates access to decision-making and advancement, multilingual professionals actively negotiate meaning through informal peer support and linguistic flexibility. The study highlights the need for healthcare institutions to move beyond rigid language policies and to recognize multilingualism as a resource. Promoting inclusive and equitable communication practices is essential for fostering collaborative, safe, and culturally responsive care in global healthcare contexts.